Feasibility of early waking cardiac arrest patients whilst receiving therapeutic hypothermia: The therapeutic hypothermia and early waking (THAW) trial. (February 2022) - Watson, Noel; Karamasis, Grigoris; Stathogiannis, Konstantinos; Potter, Matt; Damian, Max; Cook, Christopher; Pottinger, Richard; Clesham, Gerald; Gamma, Reto; Aggarwal, Rajesh; Sayer, Jeremy; Robinson, Nicholas; et al.
Abstract: Aim: To determine the safety and feasibility of an early (12 h) waking and extubation protocol for out-of-hospital cardiac arrest (OHCA) patients receiving targeted temperature management (TTM). Methods: This was a single-centre, prospective, non-randomised, observational, safety and feasibility pilot study which included successfully resuscitated OHCA patients, of presumed cardiac cause. Inclusion criteria were: OHCA patients aged over 18 years with a return of spontaneous circulation, who were going to receive TTM33 (TTM at 33 °C for 24 h and prevention of hyperthermia for 72 h) as part of their post cardiac arrest care. Clinical stability was measured against physiological and neurological parameters as well as clinical assessment. Results: 50 consecutive patients were included (median age 65.5 years, 82% male) in the study. Four (8%) patients died within the first twelve hours and were excluded from the final cohort ( n  = 46). Twenty-three patients (46%) were considered clinically stable and suitable for early waking based on the intention to treat analysis; 12 patients were extubated early based on a variety of clinical factors (21.4 ± 8.6 h) whilst continuing to receive TTM33 with a mean core temperature of 34.2 °C when extubated. Of these, five patients were discharged from the intensive care unit (ICU) <48 h after admission with a mean ICU length of stay 1.8 ± 0.4 days. Twenty-eight patients (56%) were discharged from the ICU with a modified Rankin Score of 0–2. The overall intra-hospital mortality was 50% ( n  = 25). Conclusions: It is safe and feasible to wake selected comatose OHCA patients at 12 h, allowing for earlier positive neuro-prognostication and reduced ICU stay.